2001
DOI: 10.1037/0033-3204.38.3.319
|View full text |Cite
|
Sign up to set email alerts
|

Parental overprotection in Asian American children: A psychodynamic clinical perspective.

Abstract: Parental overprotection, involving tight control of children and lack of parental warmth, although culturally tolerated in traditional Asian societies, may result in significant psychopathology for Asian children growing up in modern Western societies. The therapist working with disturbed children from Asian families with excessively overprotective parents can address the child's needs for emotional autonomy and warmth while remaining sensitive to the cultural values supporting family interdependence. The para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 37 publications
1
15
0
Order By: Relevance
“…This parenting characteristic is congruent with the description by some of Asian parenting as being facilitative (e.g. training parenting style, Chao, ), organizational (Lau & Cheung, ), overly protective (Lai, Zhang, & Wang, ; Lowinger & Kwok, ), or even authoritarian (Chiu, ; Wang, Pomerantz, & Chen, ).…”
Section: Discussionsupporting
confidence: 79%
“…This parenting characteristic is congruent with the description by some of Asian parenting as being facilitative (e.g. training parenting style, Chao, ), organizational (Lau & Cheung, ), overly protective (Lai, Zhang, & Wang, ; Lowinger & Kwok, ), or even authoritarian (Chiu, ; Wang, Pomerantz, & Chen, ).…”
Section: Discussionsupporting
confidence: 79%
“…Affectionate and open communication are generally discouraged in Asian culture (Le, Berenbaum, & Raghavan, 2002;Lowinger & Kwok, 2001). This includes physical and verbal expres-sions of love, anger, and other strong emotions and opinions.…”
Section: Communication Patternsmentioning
confidence: 99%
“…For example, parents who experience their child acculturating at a pace that far exceeds theirs may react by becoming overprotective. In fact, previous researchers have indicated that many immigrant youth, including Asian American (Lowinger & Kwok, 2001) and Asian Indian (Varghese & Jenkins, 2009) youth, perceive their parents as overprotective due, in part, to acculturation discrepancies. This study expands on these findings by examining this process in a group of Latino youth.…”
Section: Discussionmentioning
confidence: 99%